Understanding the impact of the UN convention on the rights for persons with disabilities using qualitative research methodologies - Duncan, Janet M. (Social Welfare: Interdisciplinary Approach, 2011)
The UN Convention on the Rights of Persons with Disabilities (2008) has been hailed as a breakthrough in the fi eld of human rights and advocacy for individuals with disabilities. Monitoring the implementation of the convention is a large task that will require an examination of research methodologies traditionally used in studying the effects of particular phenomena. This article argues that qualitative research methods which rely on the individual perspectives of persons with disabilities, their advocates, and family members will yield important data to further our understanding of the implementation of the convention. Additionally, we can identify best practices in the fi eld of inclusive development to assist all persons with disabilities globally.
Keywords: qualitative research; inclusive development; persons with disabilities; UN Convention on the Rights of Persons with Disabilities